Science and religion : Christian and Muslim perspectives : a record of the eighth Building Bridges Seminar convened by the Archbishop of Canterbury, Bahçeşehir University, Istanbul, 16-18 June 2009 - Marshall, David, 1963- (Washington, D.C. : Georgetown University Press, 2012)
Science and Religion is a record of the 2009 Building Bridges seminar, a dialogue between leading Christian and Muslim scholars convened annually by the Archbishop of Canterbury. The essays in this volume explore how both faith traditions have approached the interface between science and religion and throw light on the ongoing challenges posed by this issue today. The volume includes a selection of relevant texts together with commentary that illuminates the scriptures, the ideas of key religious thinkers, and also the legacy of Charles Darwin.
Commentary: The Importance of al-Ghazalı and Ibn Rushd in the History of Islamic Discourse on Religion and ScienceCharles Darwin; Introduction to Darwin and the Selected Texts; Early Arabic Views of Darwin; Modern Islamic Texts; Introduction to Qutb and al-Sha'rawı; Pope John Paul II; Commentary; Afterword; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Qurʼan -- Criticism, interpretation, etc. -- Congresses; Bible -- Criticism, interpretation, etc. -- Congresses; Coran -- Critique, interprétation, etc. -- Congrès.; Bible -- Critique, interprétation, etc. -- Congrès.; Bible; Qurʼan; Islam -- Relations -- Christianity -- Congresses; Christianity and other religions -- Islam -- Congresses; Islam -- Doctrines -- Congresses; Dogma -- Congresses; Religion and science -- Congresses; Islam -- Relations -- Christianisme -- Congrès.; Christianisme -- Relations -- Islam -- Congrès.; Islam -- Doctrines -- Congrès.; Religion et sciences -- Congrès.; Dogme -- Congrès.; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; RELIGION -- Religion & Science; Interfaith relations; Islam; Christianity; Islam -- Doctrines; Religion and science; Electronic books; Conference papers and proceedings; Criticism, interpretation, etc